2011
DOI: 10.1007/s10551-010-0720-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Organizing Between Unions and NGOs: Conflict and Cooperation Among Swedish Unions and NGOs

Abstract: code of conduct, corporate responsibility, international framework agreement, labour practice, NGO, supplier relations, transnational corporations, union,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
1
7
0
1
Order By: Relevance
“…In other words, non–employee‐oriented CSR would be part of their utility function and union leaders could be bargaining along broader lines than previously thought (Clark and Oswald 1993). This is interesting in the UK context and does mimic some of the findings from Scandinavian countries where overall unions are more entrenched (Egels‐Zanden and Hyllman 2011; Gjolberg 2009).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In other words, non–employee‐oriented CSR would be part of their utility function and union leaders could be bargaining along broader lines than previously thought (Clark and Oswald 1993). This is interesting in the UK context and does mimic some of the findings from Scandinavian countries where overall unions are more entrenched (Egels‐Zanden and Hyllman 2011; Gjolberg 2009).…”
Section: Discussionsupporting
confidence: 66%
“…Are external constituents perceived as competitors for company resources or can they be collaborators in pursuing common interests? In Sweden, where collective bargaining is broader and union density significantly higher than the United Kingdom, collaboration between unions and non‐governmental organizations (NGOs) interested in supply chains and labour rights has been successful despite difficulties (Egels‐Zanden and Hyllman 2011). In the United Kingdom, interviews by Gold et al .…”
Section: Corporate Supply and Stakeholder Demand Of Csrmentioning
confidence: 99%
“…In addition to these quantitative approaches, the IOC field has also much to gain from qualitative studies. Case studies are specifically promising to enrich our understanding of the dynamics of IOCs (e.g., Egels-Zandén and Hyllman, 2011). Longitudinal analyses allow researchers to delve deeply into the contextual factors, motives, and process involved in IOCs.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Limited empirically grounded research explores union-NGO relations [for rare exceptions, see Ford's (2009) analysis of Indonesian unions and NGOs and Kryst's (2012) analysis of the German Clean Clothes Campaign]. Still, previous research has suggested some explanations of why unions and NGOs have difficulties cooperating, highlighting organizational (Braun & Gearhart 2004;Egels-Zandén & Hyllman 2011), class-related (Ford 2009), and gender-related differences (Huyer 2004). Drawing upon the institutional logic perspective (Thornton et al 2012), we develop a complementary explanation showing that conflicts could stem from unions and NGOs acting upon multiple local institutional logics.…”
Section: Introductionmentioning
confidence: 99%